Pengaruh Layanan Guru Dalam Pembelajaran Terhadap Kepuasan Siswa Di SMP Terpadu Al-Istiqomah Kota Tasikmalaya - Ririn Nahriyah; Caswita Caswita; Husni Mubarok (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Schools is an educational instutions that is required to provide services to optimally meet student needs with the aim of creating student satisfaction. Many factors influence student satisfaction, one of which is teacher service, namely by having 5 indicators: Tangibles, Reliability, Responsiveness, Assurance and Empathy. The aims of this study were: (1) To find out the services provided by teachers to students at Al-Istiqomah Integrated Junior High School, (2) To find of out student satisfaction with student services at Al-Istiqomah Integrated Junior High School. (3) To find out how much influence teacher services have on student at Al-Istiqomah Integrated Junior High School. The thinking framework of this study is the influence of teacher services on student satisfaction as measured by the indicators of each variable. Indicators of variable (X) the effect of teacher services are Tangibles, Reliability, Responsiveness, Assurance and Empathy. And indicators of variable (Y) student satisfaction, namely student feel happy, think positively and not complaining. The research method used by researchers is a survey method with a quantitative approach that is descriptive in nature. Data collection techniques used interviews and questionnaires. The result of this study indicate that : (1) teacher services provided to Al-Istiqomah Integrated Junior High School students can be categorized as verygood with indicators of tangibles, reliability, responsivenees, assurance, and empathy. From the result of the respondents’ answers a value of 60% was obtained from all respodents who gave the highest score, namely 5( always ) an average score of 4,2 with a very good category.(2) student satisfaction felt at Al-Istiqomah Integrated Junior High School could be categorized as very good with happy indicators, positive thinking, ang no complaints. From the result of therespondents’ answersa value of 70% was obtainedfrom all respondents who gave the highest score, namely 5 (always). The average score was 4,5in the very good category. (3)there is an influence of teacher services on student satisfaction based on the result of regression calculations with a value of 0,594, so that the alternative hypothesis Ho is rejected and Ha is accepted. Meanwhile, the influence of teacher services on student satisfaction based on the calculation of the coefficient og determination ang non determinaton accounts for 35%.